Racial Profiling and Moral Responsibility for Racialized Crime - Gordon, Tiffany M. (My University, 2016)
This thesis began (in thought) as a response to the killing of Trayvon Martin in 2012 and that of Mike Brown not too long after, and the many victims who succumbed to some form of racial profiling of another before these deaths, in-between, and after. Desmond Cole wrote an article in 2015 that further precipitated the thought into action and the desire to address racial profiling in writing form. In the thesis I take a philosophical approach to racial profiling, and although in the first two chapters I address the ordinary discussions surrounding racial profiling, in the latter two I tackle the problem of moral responsibility which I take to be central. In the first part of the thesis I defend the policy in the case of illegal weapons possession based on Henry Shue’s principle of basic rights, but in the latter part I question this assertion. Even if blacks were shown to commit more of certain crimes or even violent crimes, that does not address the fact that crime arises out of context and in the case of “black crime” out of a racialized context. In the latter part of the thesis I work through the problem of collective and personal moral responsibility, eventually maintaining that not only is reparations just, but for racial profiling to be justified investment must be made into racialized communities with high rates of poverty. This is because collective responsibility must be taken for the societal oppression and discrimination that has partly resulted in high rates of racialized crime.
Keywords: philosophy of race, racism, racial profiling, moral responsibility, collective moral responsibility, personal moral responsibility, social inequality, systemic inequality, morality